Adaptive tacholess order tracking method based on generalized linear chirplet transform and its application for bearing fault diagnosis. (August 2022) - Duan, Rongkai; Liao, Yuhe; Yang, Lei
Abstract: Bearing plays an important role in industrial equipment and it may operate under varying conditions. When the speed of shaft changes, whether monotonous or non-monotonous speed, common diagnostic approaches cannot effectively extract fault features. But encoders and tachometers are not always available. Therefore, tacholess order tracking methods which can directly extract the instantaneous rotating frequency (IRF) from vibration signal are very useful in bearing fault diagnosis under varying speed. Among these methods, the generalized linear chirplet transform (GLCT) can produce time–frequency representation without constructing any mathematical model, but there are two parameters must be set in advance. The parameters have great influence on the analysis result. To reduce the dependence on the prior knowledge of presetting the parameters in varying conditions, two different improved GLCT methods are proposed in this paper. To do with the situation where the trend of speed changes is monotonous, the scale-space is introduced to lift GLCT which can adaptively set a vital parameter, and the other parameter is set to default value. When faced with non-monotonous speed, the second method is proposed which the grey wolf optimizer (GWO) and Gini index are introduced to search the optimal parameters of GLCT without any prior knowledge. With the help of the proposed methods, the IRF can be extracted directly from vibration signal. Then, the raw signal can be resampled based on the IRF to eliminate the influences of speed. The morphological filtering is adopted to remove the noise and extract the fault characteristics order (FCO). Another two typical time–frequency analysis methods are used for comparisons. Three different signals are used for analysis to demonstrate the superiority of the proposed methods. Highlights: Two tacholess order tracking methods are proposed based on GLCT to extract the instantaneous rotation frequency directly. Scale-space is introduced into GLCT to adaptively determines the value of N . Grey wolf algorithm and Gini index are adopted to lift GLCT.